If Immigrants Could Vote in the UK: A Thought Experiment with Data from the 2015 General Election. Issue 4 (28th September 2016) - Fox, Sean; Johnston, Ron; Manley, David
Abstract: The distribution of voting rights in the UK is an artefact of history rather than a product of clear legal or philosophical principles. Consequently, some resident aliens (i.e. immigrants) have the right to vote in all UK elections; others can vote in local elections but are excluded from national elections; still others are excluded from all elections. In England and Wales alone, roughly 2.3 million immigrants are excluded from voting in national elections. This exclusion is inconsistent with the founding principle of democracy and distorts political discourse. What if all immigrants could vote in national elections? We estimate that up to ninety‐five parliamentary seats could have been won by a different party in the 2015 general election. More substantially, enfranchising all immigrants would require re‐drawing UK constituency boundaries. The new electoral map would increase the relative power of urban constituencies and would incentivise some political entrepreneurs and parties to temper anti‐immigration rhetoric.